THE COMPERATIVE STUDY OF THE QUALITY OF GRILLED CATFISH (Pangasius hypophthalmus) - Raja Tayib; N Ira sari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to determine the differences in the quality of grilled catfish with different ingredients. The treatments consisted of coconut shell fuel (A), coconut shell charcoal fuel (B). The parameters observed were pH, total phenol test, and total acid test. Based on the research results, it can be concluded that grilled catfish with different fuels have a significant effect on the total phenol value and the total acid value. The best treatment from the research results was grilled catfish using coconut shell charcoal as fuel with an average value of pH (6.4), total phenol (8.97 ppm), and total acid (0.57%). Keywords : Catfish, Coconut shell charcoal, Grilling fish